First report of secondary metabolites, Violaceol I and Violaceol II produced by endophytic fungus, Trichoderma polyalthiae and their antimicrobial activity - Katesaraporn Nuankeaw (2020)
© 2019 The Mycological Society of Japan Bioactive compounds of endophytic fungus Trichoderma polyalthiae were extracted from culture broth media. The crude extracts showed strong antimicrobial activity against human pathogens. Biologically active compounds were isolated and purified by chromatographic methods. The structures of the pure compounds were elucidated by spectroscopic methods. They were identified as Violaceol I and Violaceol II. These compounds were detected as secondary metabolites produced by this genus for the first time. Violaceol I and II had a broad spectrum of antimicrobial activity against human pathogens, including Gram-positive bacteria (Staphylococcus saprophyticus, Staphylococcus aureus, Methicillin-Resistant S. aureus, Bacillus subtilis, Bacillus cereus) and Gram-negative bacteria (Salmonella typhimurium, Shigella sonnei) and Candida albicans. Violaceol I exhibited Minimal Inhibitory Concentration (MIC) values (<9.765–156.25 μg/mL) that were higher than Violaceol II (<9.765–312.5 μg/mL). Additionally, the MIC value of the phenol violaceol from this taxon was lower than the previous reports.